Ameliorating the profound gender wage gap in the architecture, engineering and construction (AEC) industry among the APEC members : The could and should - Gan, Su Ling; Chai, Chang Saar; Bibiana Lim, Chiu Yiong; Lu, Shao Ming; Gui, Hun Chuen (Asia Business Research Corporation Ltd, 2024)
This research aims to discover the challenges and propose effective strategies to empower women by ameliorating the gender wage gap in the architecture, engineering and construction (AEC) industry among the APEC members. The study applied document review analysis and conducted focus group discussions, where thirty female professionals in the AEC industry from APEC participated. The results report four challenges contributing to the gender wage gap, namely gender bias and stereotyping, work-family conflicts, physical strength and lack of transparency. Based on the challenges, the study suggests several key strategies focusing on women's participation in the AEC industry, encouraging gender-friendly workplaces, healthy and safe workplaces, and fair career development opportunities to reduce the gender wage gap effectively. The findings suggest that by increasing awareness of the value of women's involvement in the AEC industry, pragmatic policies should be formulated for APEC members to break down the barriers to the gender wage gap.